Relation Between Pancasila and Islamic Values on Religious Freedom - Sulasman Sulasman; Eki Kania Dewi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
The discourse of religious harmony and freedom is still a current study and much studied through various approaches, including in the perspective of history, sociology, and culture. In Indonesia, normatively, the practices of religious harmony and freedom are referred to both Islamic religion and Pancasila values. The two normative references are positioned in line. Thus, even for the people, Pancasila has a spirit of Islam, because the framers of Pancasila (and Konstitution UUD 1945) are Moslem like Muhammad Yamin and Sukarno. Consciously or not, the Islamic teaching viewed by those framers of Pancasila absorbed into the values of Pancasila. Therefore, it is fair enough that Pancasila and Islam have harmony and conformity, including the concepts of religious harmony and freedom.